Cationic guests direct molecular capsule formation and the impact towards the extended self-assembly in combinatorial supramolecular systems. Issue 4 (3rd April 2021) - Ling, Irene; Sobolev, Alexandre N.; Dalgarno, Scott J.
ABSTRACT: Four multi-component complexes based on p -sulfonatocalix[4]arene anion, the methyltriphenylphosphonium cation, lanthanide ions (Gd(III)) and different ionic liquid-based cations (1-methyl-3-butylimidazolium, 1-methyl-3-octylimidazolium and 1, 4-bis((3-methylimidazolidinyl)methyl)benzene) were synthesised and structurally characterised. Common bilayer arrangements are formed in the extended structures of all four complexes, though the bilayer thicknesses varies depending on the components involved. Molecular capsule formation is facilitated by the inclusion of methyltriphenylphosphonium, 1-methyl-3-butylimidazolium and 1, 4-bis((3-methylimidazolidinyl)methyl)benzene cations, but not in the case of the 1-methyl-3-octylimidazolium cation. Molecular capsule size depends on the nature of the included guest cation, and methyltriphenylphosphonium cations fill compact spaces between calixarenes in these new bilayer arrays. GRAPHICAL ABSTRACT: uf0001